1999
DOI: 10.1046/j.1460-9568.1999.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of bistratified cell IPSPs and basket cell IPSPs by pentobarbitone sodium, diazepam and Zn2+: dual recordings in slices of adult rat hippocampus

Abstract: Simultaneous intracellular recordings from presynaptic Stratum pyramidale interneurons and postsynaptic pyramidal cells in adult rat hippocampal slices were performed to investigate the strength of the modulation of single-axon inhibitory postsynaptic potentials (IPSPs) by the GABAA receptor modulators pentobarbitone, diazepam and zinc. The processing of biocytin-filled interneurons for light microscopy revealed that these single-axon IPSPs were generated by basket cells (n = 33), bistratified cells (n = 18) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
82
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 44 publications
(81 reference statements)
8
82
0
1
Order By: Relevance
“…All CA1 basket cells in this study displayed similar dendritic and axonal patterns and resembled those reported previously (Sik et al, 1995;Freund and Buzsaki, 1996;Ali et al, , 1999Pawelzik et al, 1999). They had relatively narrow vertically oriented dendritic arbors that extended through SO, in some cases entering the alveus, and through SR and into SLM (Fig.…”
Section: Dendritic and Axonal Arbors Of Ca2 Basket Cells: Comparison supporting
confidence: 86%
See 3 more Smart Citations
“…All CA1 basket cells in this study displayed similar dendritic and axonal patterns and resembled those reported previously (Sik et al, 1995;Freund and Buzsaki, 1996;Ali et al, , 1999Pawelzik et al, 1999). They had relatively narrow vertically oriented dendritic arbors that extended through SO, in some cases entering the alveus, and through SR and into SLM (Fig.…”
Section: Dendritic and Axonal Arbors Of Ca2 Basket Cells: Comparison supporting
confidence: 86%
“…All dendrites were aspiny and were often beaded. CA1 basket cell axons whose major branches were often myelinated, ramified extensively in SP, and, in some cases, in the most proximal regions of SR and SO (previously described as "wide arbor basket cells") (Buhl et al, 1996;Freund and Buzsaki, 1996;Pawelzik et al, 1999Pawelzik et al, , 2002. The majority of these CA1 basket cells were found to be PV immunopositive and CB immunonegative (16:23).…”
Section: Dendritic and Axonal Arbors Of Ca2 Basket Cells: Comparison mentioning
confidence: 95%
See 2 more Smart Citations
“…This activity might lead to a suppression of the majority of cells (Dragoi et al, 1999) and disrupt the generation of theta oscillations. Their local axons in the CA1 area innervate pyramidal cell dendrites, as shown here (but see Gulyas et al, 2003), and cooperatively release GABA with the bistratified cells, which fire at high frequency (Klausberger et al, 2004) during the ascending phase of the extracellular ripple cycle and innervate the same pyramidal cell domains acting on GABA A receptors (Pawelzik et al, 1999). Together, they temporally structure the excitation of the CA3 input in CA1 pyramidal dendrites at ripple frequency.…”
mentioning
confidence: 55%